Retención de catéter epidural con formación de nudo en canal medular: Reporte de un caso - Mara Patricia Ruiz-Moreno; Francisco Arroyo-Martínez; Sahara Livier Yañez-Cortez; Marisela Arrieta-Contreras (Critical Care & Emergency Medicine, 2026)
Epidural catheter rupture and retention is an uncommon complication of neuroaxial anesthesia, with an estimated incidence between 0.002% and 0.005%. It is associated with factors such as excessive catheter insertion, kinking, entrapment between anatomical structures (ligamentum flavum, articular facets, or spinous processes), resistance to traction, and inadequate maneuvers during removal. We present the case of a 76-year-old male with multiple comorbidities who underwent radical prostatectomy under balanced general anesthesia combined with peridural blockade. The procedure proceeded without incidents, and continuous analgesia was maintained via an elastomeric pump. On the first postoperative day, during catheter removal, resistance occurred and the catheter fractured. Lumbar tomography revealed a fragment approximately 56 mm in length at the L3 level within the spinal canal. According to the literature, management of retained fragments is controversial. In asymptomatic patients, close monitoring may be chosen since the material is inert; however, there is risk of migration, formation of granulation tissue, and dural adhesions, which can complicate delayed extraction and increase the risk of neurological sequelae. In this case, following neurosurgical evaluation, surgical removal via a posterior L3-L4 approach was decided, achieving complete extraction of the fragment. The patient progressed without neurological deficit and was discharged with scheduled follow-up. This case reinforces the importance of informing the patient, performing timely imaging studies, and individualizing management to prevent late complications.